Business Law Perspective on Marketing Activities of Limited Liability Companies in Indonesia - Ryan Rudyarta (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
Marketing activities of limited liability companies (LLC) in Indonesia are not merely business strategies but also legal activities that entail juridical consequences. The increasingly complex dynamics of modern marketing, including digital marketing, e-commerce, and the utilization of consumer personal data, demonstrate that marketing activities cannot be separated from business law regulations, whether related to consumer protection, fair competition, electronic information, or personal data protection. Marketing by LLC in Indonesia is regulated by various laws aimed at creating fair, transparent transactions while avoiding practices that could harm consumers. From a business law perspective, marketing in Indonesia, especially within limited liability companies, plays a crucial role in maintaining the smooth operation of businesses that benefit not only the company but also the wider society, including consumers. Marketing activities by LLC must consistently adhere to the principles of law, including consumer protection and the obligation to ensure transparency in every promotional activity or advertisement. This study employs a normative juridical method with both statutory and conceptual approaches. The analysis is conducted qualitatively through systematic and teleological legal interpretation, supported by secondary legal materials such as academic literature and recent scholarly articles on business law and marketing. The findings reveal that marketing activities of limited liability companies are closely intertwined with business law, as all contracts, promotions, and marketing strategies constitute legal acts that must adhere to the principles of honesty, transparency, and fair competition. Revenue growth through effective marketing can only be achieved sustainably if it is designed in accordance with the principles of good corporate governance and legal compliance. Thus, marketing in the perspective of business law functions not only as a commercial tool but also as an instrument for creating legitimate, ethical, and equitable value for both the company and society.